Design And Construction Of The Website For The Information And Service Center Of Cihaurbeuti State SLB - Jajat Sudrajat; Toni Kusnandar; Lilis Emalia; Dheni Apriantsani Budiman; Oktavia Oktavia (LPPM STMIK Mardira Indonesia, 2025)
This community service initiative aims to create and implement a website that serves as an information hub and service platform for SLB Negeri Cihaurbeuti Ciamis, catering to students with special needs. The school faces challenges such as limited access to information, delays in data transmission, and inaccuracies that hinder communication among students, teachers, and parents. This activity employs a qualitative methodology with a case study design, incorporating comprehensive interviews and participatory observation to collect insights from all stakeholders. The findings of this activity reveal a critical necessity to revise the current information system and establish a more effective web-based platform. All stakeholders anticipate a cohesive, intuitive system that enhances communication and information dissemination. This program effectively demonstrated that digital technology can improve information accessibility and modernize communication practices in the educational setting. This community service initiative aims to lay the groundwork for subsequent advancements in information systems at SLB Negeri Cihaurbeuti and other educational institutions to enhance the quality of inclusive education.